Features of COPD patients by comparing CAT with mMRC: a retrospective, cross-sectional study - Huang, Wei-Chang (NPJ Prim Care Respir Med, 2015)
BACKGROUND: The group assignment of chronic obstructive pulmonary disease (COPD) may differ depending on whether the COPD assessment test (CAT) or modified Medical Research Council dyspnoea scale (mMRC) is used. AIMS: This study intended to clarify how different patient characteristics influence the differences, to determine the relationships between CAT and mMRC and to characterise COPD patients by both CAT and mMRC. METHODS: This was a retrospective, cross-sectional study. The data, collected by Taiwan Obstructive Lung Disease consortium, were managed and analysed. RESULTS: Of the 757 participants, COPD group assignment was not identical as well as no substantial agreement presented when categorised based on the cut-point CAT score ⩾10 and each mMRC cut-point. In all, 38.2% of participants had discordant group assignments together with a lower mean CAT score, less severe airway obstruction and less severe airflow limitation compared with those with concordant group assignments. In the discordant group, the CAT⩾10/mMRC 0–1 subgroup had more wheezing than CAT<10/mMRC⩾2 subgroup. Only moderate correlations existed between CAT and mMRC. More-symptom groups and combined high-risk group had better correlations than less-symptom groups and combined low-risk group, respectively. A modest negative correlation existed between forced expiratory volume in 1 s percentage (FEV(1)%) predicted and CAT score and between FEV(1)% predicted and mMRC scale in parallel with a significant positive relationship existing between the CAT score and mMRC scale. Notably, a significant proportion of COPD patients with each scale of mMRC had health status impairment. CONCLUSIONS: The Global initiative for Chronic Obstructive Lung Disease committee should redefine the applications of CAT and mMRC in the management of COPD.